Phytochemical Screening and Nanoherbs Synthesis of Ethanol Extract of the Butterfly Pea Flower (Clitoria ternatea L.) with its Characterization - Achrifa, Silfia Indah; Suyatno, Suyatno (Jurnal Pijar Mipa, 2024)
Every plant has a different secondary metabolite content, influenced by the location and conditions where the plant grows. Preparations from the butterfly pea flower (Clitoria ternatea L.) extract form have poor bioavailability. One effort to overcome this problem is by formulating it into nanoherbs form. This research aims to determine the phytochemical content and synthesize nanoherbs ethanol extract of butterfly pea flowers. The butterfly pea flowers were extracted using the maceration method, and the resulting thick purplish blue extract was 145.254 grams. The thick extract was analyzed for secondary metabolite content using phytochemical screening, and it was found to contain alkaloids, flavonoids, saponins, triterpenoids, and tannins. Nanoherb synthesis uses the ionic gelation method with an alginate polymer and a CaCl2 cross-linking agent. The synthesis result is a purple nanoherbs colloid with optimal variations in the ratio (10:1). The synthesized nanoherbs were characterized using PSA and obtained particle size results from the optimal variation of 220.4 nm, polydispersity index 0.2550, and zeta potential of -22.5 mV.